PENGARUH KONSENTRASI PGPR DAN PUPUK NPK TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis Guineensis JACQ) DI MAIN NURSERY. - Syahputra, Andrian; Razali, Razali; Ramadhan, Ali (Agrobun, 2025)
The purpose of this study was to determine the growth response of oil palm seedlings in the main nursery to the provision of PGPR and NPK fertilizer. The research was carried out in Selayang Village, Selesai District, Langkat Regency, North Sumatra in December 2023 until completion. The research used a factorial randomized block design (RAK) with 2 treatment factors. where the first factor is PGPR with 3 levels: P0 (0 ml) P1 (40 ml) P2 (50 ml). while the second factor is NPK fertilizer with 3 levels: N0 (0 gr) N1 (5 gr) N2 (10 gr). The parameters observed were plant height (cm), stem diameter (mm), number of leaves (strands) and leaf area (cm2). The effect of PGPR gave real results on plant height parameters at ages 11, 13, 15, 17, 19, 21 .23 WAP, stem diameter at ages 11, 13, 15, 17, 19, 21, 23 WAP, leaf area at ages 15, 17, 19, 21, 23 WAP. Providing NPK fertilizer had a significant effect on plant height at 5, 7, 9 WAP, stem diameter at 11, 13, 15, 17, 19, 21, 23 WAP, and leaf area at 5 and 7 WAP. as well as interactions that showed no significant impact on plant height, stem diameter, number of leaves and leaf area.